THE EFFECT OF INTERPERSONAL COMMUNICATION TRAINING ON THE PREVENTION OF AGGRESSIVE BEHAVIOR - Eka Aryani; Abdul Hadi; Anifa Tuzzuhroh Nurbaiti (Jurnal Penelitian Bimbingan dan Konseling, 2024)
This research aims to determine the effect of interpersonal communication training on preventing aggressive behavior. The subjects of this research were students of Vocational School The data collection tool used was the aggressive behavior scale. The research subjects used as samples were 20 people from a population of 100 vocational school students. This number was obtained from students at Vocational School which means it is not significant. In the aspect of verbal aggression, z = -1.477 with p > 0.05 (p = 0.140, 2 tail; p = 0.70 1 tail) which means it is also not significant. The analysis of differences for the anger aspect was also not significant z = -0.557 with p > 0.05 (p = 0.564, 2 tail; p = 0.282, 1 tail). A new significant difference was found in the hostility aspect which was indicated by z = -2.138 with p < 0.05 (p = 0.033, 2 tail; p = 0.0165, 1 tail). The research results show that interpersonal communication training has an effect on preventing aggressive behavior.